Strategi Pengembangan Usaha UMKM Kuliner Di Kota Pekanbaru - Rosmita Rosmita; Lilis Surianti; Herman Herman; Arya Teguh Adera (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this research is to analyze and explain the business development strategies of culinary MSMEs in Pekanbaru City. The method used in this research is to use a qualitative descriptive method that describes the reality of culinary businesses with a focus on development strategies. Data collection tools by prioritizing interviews, observation and documentation. After collecting field data, the authors will distinguish primary and secondary data. The data analysis technique used is the author collects data, which is then thoroughly analyzed and concluded to find out the strategies used in the development of Pekanbaru City Culinary MSMEs. The results of the study found that the need for strategies for Pekanbaru City Culinary MSMEs to identify strengths, weaknesses, opportunities and challenges related to capital, business innovation, utilization of social media and so on. in the future, more attention needs to be paid from related agencies so that Pekanbaru City MSMEs continue to exist such as capital, product innovation to social media utilization.. Keywords: Strategy, Business Development, UMKM, Culinary